Converging on the orb: denser taxon sampling elucidates spider phylogeny and new analytical methods support repeated evolution of the orb web. (29th October 2020) - Kallal, Robert J.; Kulkarni, Siddharth S.; Dimitrov, Dimitar; Benavides, Ligia R.; Arnedo, Miquel A.; Giribet, Gonzalo; Hormiga, Gustavo
Abstract: High throughput sequencing and phylogenomic analyses focusing on relationships among spiders have both reinforced and upturned long‐standing hypotheses. Likewise, the evolution of spider webs—perhaps their most emblematic attribute—is being understood in new ways. With a matrix including 272 spider species and close arachnid relatives, we analyze and evaluate the relationships among these lineages using a variety of orthology assessment methods, occupancy thresholds, tree inference methods and support metrics. Our analyses include families not previously sampled in transcriptomic analyses, such as Symphytognathidae, the only araneoid family absent in such prior works. We find support for the major established spider lineages, including Mygalomorphae, Araneomorphae, Synspermiata, Palpimanoidea, Araneoidea and the Retrolateral Tibial Apophysis Clade, as well as the uloborids, deinopids, oecobiids and hersiliids Grade. Resulting trees are evaluated using bootstrapping, Shimodaira–Hasegawa approximate likelihood ratio test, local posterior probabilities and concordance factors. Using structured Markov models to assess the evolution of spider webs while accounting for hierarchically nested traits, we find multiple convergent occurrences of the orb web across the spider tree‐of‐life. Overall, we provide the most comprehensive spider tree‐of‐life to date using transcriptomic data and use new methods to explore controversial issues of web evolution, including the origins and multiple losses of the orb web.